Comparison of phenol-formaldehyde and lignin-formaldehyde resin adhesives for wood application - Muhammad Nor Arifin, Yaakob; Rasidi, Roslan; Nurjannah, Salim; Sarani, Zakaria (Trans Tech Publications Ltd, Switzerland, 2021)
Phenolic resins are thermosetting material that is commercially produced via the condensation process of phenol and formaldehyde. However, due to the usage of petro-based materials in the production of phenolic resins, several approaches have been made, and one of the approaches is by substituting the raw materials, especially phenol, with lignin. In this study, acetosolv lignin was used to produce lignin-formaldehyde (LF) and compared with phenolformaldehyde (PF) resin. The resinification reaction was conducted at 85 °C for 4h. The functional group, curing behavior and the shear strength of the resins was analyzed using FTIR-ATR, DSC and Universal Testing Machine, respectively. The formation of PF and LF resins was confirmed by the presence of the methylene bridge functional group at 1460 cm-1. The curing curve shows the shift of LF resin to a higher temperature compared to the PF resin. Furthermore, the evaluation of bonding strength shows that LF resin possesses a low shear strength compared to PF resin. However, both resins pass to be adhesives for the manufacture of plywood panels based on standard JIS K-6852.